The Impact of Knowledge Sharing and Participative Decision-Making on Employee Turnover Intention: The Mediating Role of Perceived Organizational Support. (October 2022) - Fattah, Jinan; Yesiltas, Mehmet; Atan, Tarik
In order for an organization to thrive and operate well, it is dependent on its ability to share knowledge. It is consequently well accepted that knowledge sharing in companies is a key success factor for enhancing company performance and sustainability. Therefore, knowledge sharing and employee participation in decision-making are positively associated with perceived organizational support, and turnover intention. Notwithstanding, the inherent advantages of knowledge sharing and participative decision making, promoting organizational support is a concern for many organizations. As such, the purpose of this study is to examines the interaction between knowledge sharing, participative decision-making, and turnover intention, mediated by perceived organizational support using a structural equation model. The result of the analysis of data collected from 323 staffs of telecommunication company in Iraq indicated that perceived organization support mediates the relationship between knowledge sharing, participative decision making, and turnover intention. Furthermore, knowledge sharing and participative decision making affect turnover intention. This study was able to infer that emolyees who are considered, recognized and treated positively benefit the organization, and this eliminates any intent to leave.